Faunal content of lower Pliocene Çayba?i Formation and its relationship with depositional environments, Eastern Elazi?/Turkey - Taşgin, Calibe Koç; Nazik, Atike; Islamo?lu, Yeşim; Türkmen, Ibrahim (Hacettepe Universitesi Yerbilmleri, 2012)
Çayba?i Formation is located in the eastern Taurid Tectonic Unit. The unit was deposited in alluvial fan, fluvial, delta and lacustrine environments. Although alluvial fan and braided river deposits do not contain fossils, low-sinuosity river, delta and lacustrine deposits contain ostracod, gastropod and pelecypod fossils. Kör Tepe, ÇardakdivarTepe, Hacisam Dere and Ziyaret Tepe measured sections that have time and space relationships consist of low-sinuosity river and delta-lacustrine facies and contain Candona, llyocypris, Cyprideis and Heterocypris species of ostracod fossils and Valvata, Lymnaea, Tinyyea, Planorbis, Radix, Gyraulus, Hydrobia, Potomida, Unio, Margaritifera, Anadonta ve Leguminaia species ofmollusc fossils. Moreover, different levels of Ziyaret Tepe and Kör Tepe measured section comprise Charophytes fossils. Environmental features of ostracod and mollusc species are in agreement with sedimentological data of the unit, deposited in fluvial, delta-lacustrine environments during Early Pliocene.
Alt Pliyosen Çayba?i Formasyonu'nun faunal içeri?i ve çökelme ortamlari ile ilişkisi, Elazi? Do?usu/Türkiye
Keywords: Delta-lacustrine; Early Pliocene; Elazi?; Fluvial; Lithostratigraphy; Mollusc; Ostracod